Assessment of Serum Zinc Levels of Patients with Thalassemia Compared to Their Siblings - Mohamed El Missiry; Mohamed Hamed Hussein; Sadaf Khalid; Naila Yaqub; Sarah Khan; Fatima Itrat; Cornelio Uderzo; Lawrence Faulkner (Anemia)
Zinc (Zn) is essential for appropriate growth and proper immune function, both of which may be impaired in thalassemia children. Factors that can affect serum Zn levels in these patients may be related to their disease or treatment or nutritional causes. We assessed the serum Zn levels of children with thalassemia paired with a sibling. Zn levels were obtained from 30 children in Islamabad, Pakistan. Serum Zn levels and anthropometric data measures were compared among siblings. Thalassemia patients’ median age was 4.5 years (range 1–10.6 years) and siblings was 7.8 years (range 1.1–17 years). The median serum Zn levels for both groups were within normal range: 100 μg/dL (10 μg/dL–297 μg/dL) for patients and 92 μg/dL (13 μg/dL–212 μg/dL) for siblings. There was no significant difference between the two groups. Patients’ serum Zn values correlated positively with their corresponding siblings (r=0.635, P<0.001). There were no correlations between patients’ Zn levels, height for age Z-scores, serum ferritin levels, chelation, or blood counts (including both total leukocyte and absolute lymphocyte counts). Patients’ serum Zn values correlated with their siblings’ values. In this study, patients with thalassemia do not seem to have disease-related Zn deficiency.